2019
DOI: 10.3389/fneur.2019.00924
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Biomaterial-Based Approaches as Therapies for Ischemic Stroke: A Systematic Review and Meta-Analysis of Pre-clinical Studies

Abstract: Background: In recent years pre-clinical stroke research has shown increased interest in the development of biomaterial-based therapies to promote tissue repair and functional recovery. Such strategies utilize biomaterials as structural support for tissue regeneration or as delivery vehicles for therapeutic agents. While a range of biomaterials have been tested in stroke models, currently no overview is available for evaluating the benefit of these approaches. We therefore performed a systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…Direct support of recovery processes can be achieved by inserting biomaterials such as hydrogels or living scaffolds which promote a permissive environment and/or may be used to deliver cells or bioactive molecules. 30 …”
Section: Principle Possibilities To Foster Post-stroke Recoverymentioning
confidence: 99%
“…Direct support of recovery processes can be achieved by inserting biomaterials such as hydrogels or living scaffolds which promote a permissive environment and/or may be used to deliver cells or bioactive molecules. 30 …”
Section: Principle Possibilities To Foster Post-stroke Recoverymentioning
confidence: 99%
“…A recent meta-analysis found that biomaterialbased interventions have led to lesion volume reduction and improved neurological outcomes in stroke rodent models. 162 Hydrogels act as 3D scaffolds that improve stem cell survival and differentiation, both in vivo and in vitro. 163 However, they must be finely engineered for optimal cell delivery.…”
Section: Biomaterialsmentioning
confidence: 99%
“…This highlights the need to optimize these biomaterials for stem cell viability, differentiation, and proliferation. A recent meta-analysis found that biomaterialbased interventions have led to lesion volume reduction and improved neurological outcomes in stroke rodent models [ 162 ].…”
Section: Improvement Of Stem Cell Application In Ischemic Brain Injurmentioning
confidence: 99%
“…Most studies administered hydrogels days or weeks after stroke, while few studies investigated hydrogel administration earlier than 24 h post‐IS. [ 66 ] The difference in approaches for hydrogel treatment in IS versus ICH and TBI is noteworthy and future studies in ICH should consider delayed treatment paradigms.…”
Section: Study Design: Time Of Administrationmentioning
confidence: 99%